Kritik Sastra terhadap Puisi yang Dihasilkan AI oleh Siswa SMP Unismuh Makassar - Ulviani, Maria; Kemala, Rosmalina; Rimang, Siti Suwadah; Haslinda, Haslinda; Amin, Sulvahrul (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
The development of artificial intelligence (AI) in the field of education has opened new opportunities in literary learning, particularly in the processes of poetry creation and analysis. This study aims to examine literary criticism of AI-generated poems produced by students of SMP Unismuh Makassar in order to understand the relationship between human creativity and technology. The research employs a descriptive qualitative method with modern literary criticism and semiotic approaches. The data, consisting of AI-generated poems and students’ poems, are analyzed based on linguistic, aesthetic, and moral aspects. The results indicate that AI-generated poems tend to have more orderly linguistic structures but are emotionally flatter, whereas students’ poems are more expressive and contextual. The analysis shows that literary criticism approaches are able to distinguish the depth of meaning and human values between digital works and human-created works. This study emphasizes the importance of integrating AI as a reflective and creative medium in literature learning at the secondary school level.